Stabilization / solidification, an alternative for the safe deposition of heated metals saturated sludges (2008)
Nowadays, electroplating industry generates effluents on a large scale polluted with high concentrations of cyanide and heavy metals (Cu, Ni y Zn). As an alternative to solve this environmental problem, cyanide is reduced by means of an oxidation with sodium hypochlorite and metal ions are chemically precipitated. From both processes an effluent free of pollutants is obtained, but sludge catalogued by the Instituto de Hidrología, Meteorología y estudios ambientales (IDEAM) and the Toxicity Characteristic Leaching Procedure (TCLP) as toxic and dangerous wastes (because of its high concentration of heavy metals) is generated as well. A process for diminishing the toxicity of the above mentioned solid waste by means of a stabilization/solidification process in a Portland cement matrix is proposed in this research work. This way, the sludge could be safely disposed in a rubbish dump. The obtained results show that decreasing migration of metal ions from loaded sludge in a matrix of Portland cement, fine sand and gravel to the environment, down to a level below the official regulations is possible (Decree 1594 of June 26 1984 the Ministry of Agriculture of Colombia).. The influence of the time setting was studied, a total time of 28 days was considered, Monoliths of high structural integrity which evidence values of 3000 psi of compressive strength.